Study on the change of polyphenol compounds in the pericarp of posthavest Thanh Ha litchi fruits - Thu, Nguyen Xuan; Thiet, Nguyen Van; Tuyen, Do Thi (Academia Journal of Biology, 2015)
The colour change of pericarp of postharvest litchi fruits is related to the formation of melannin, that is caused by enzymes involving in catalysis of melanin biosynthesis pathway in the litchi pericarp, in this respect polyphenol oxidase (PPO) enzyme is the most important one. This enzyme is involved in the first and the second reactions of the melanin biosynthesis reaction chain. PPO substrates are polyphenol compounds which can be found in litchi pericarp as anthocyanins and flavonoids. The results of our experiments showed that the concentration of melanin in lychee pericarp in 180 hours after being harvested increased by 7.169 times at the room temperature and by 5.05 times at 8oC. Total polyphenol content after 180 hours at room temperature and at 8oC remains 19.2% and 17.66%, respectively. The anthocyanin content after 180 hours almost completely lost at room temperature and remains 69.03% at 8oC. Total flavonoid content after 180 hours at room temperature and at 8oC remains 31.78% and 46.92%, respectively.